2006
DOI: 10.1063/1.2360143
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectromechanical nonvolatile memory device incorporating nanocrystalline Si dots

Abstract: A nanoelectromechanical device incorporating the nanocrystalline silicon ͑nc-Si͒ dots is proposed for use as a high-speed and nonvolatile memory. The nc-Si dots are embedded as charge storage in a mechanically bistable floating gate. Position of the floating gate can therefore be switched between two stable states by applying gate bias. Superior on-off characteristics are demonstrated by using an equivalent circuit model which takes account of the variable capacitance due to the mechanical displacement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Therefore, the conclusions in this paper would also be applicable to the systems mentioned in the Introduction. 2,4,6,7 In addition, the similar reduction of the ADP scattering potential might emerge in other structures, such as the SiQW embedded in SiO 2 and a silicon slab sandwiched by SiO 2 . As electrons travel only within Si region in these cases, the reduction of the ADP scattering potential might lead to significant mobility enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the conclusions in this paper would also be applicable to the systems mentioned in the Introduction. 2,4,6,7 In addition, the similar reduction of the ADP scattering potential might emerge in other structures, such as the SiQW embedded in SiO 2 and a silicon slab sandwiched by SiO 2 . As electrons travel only within Si region in these cases, the reduction of the ADP scattering potential might lead to significant mobility enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another report proposes a nano electromechanical memory device using nc-Si dots embedded in a self-supporting SiO 2 beam. 7 However, the electrical/ mechanical properties of such systems have yet to be well understood. In particular, the electron-phonon interaction is of great importance because it is the main concern for roomtemperature device operation.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their extremely small size, these nanometer scale structures possess unique properties that differ from their parent bulk material͑s͒, [1][2][3][4] which make them potential candidates for various advanced magnetoelectronic devices. [5][6][7][8] Further device development may well depend on a better understanding of various dynamic magnetic phenomena in such nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the use of a nanoelectromechanical system (NEMS) as a memory element has been demonstrated in a number of experimental investigations [1][2][3][4][5][6][7][8] . It has been suggested that in order to increase the frequency of operation, oscillatory states (cycles) should be used as the stationary states of memory elements, with consequential switching between two cycles.…”
mentioning
confidence: 99%
“…Such oscillatory states are principally different from the stationary states, i.e. fixed points -traditionally used in the majority of digital processing and storage devices 2,3,9 , and the analysis of the oscillatory states is much more challenging 10,11 .…”
mentioning
confidence: 99%